Approaches to diversion of child offenders in South Africa: a comparative analysis of programme theories - Steyn, Francois (University of the Free State, 2010)
Diversion of children in conflict with the law has been practiced in South Africa since the early 1990s. From that time, the number of referrals and the scope of programmes burgeoned despite the absence of legislation to regulate diversion. The Child Justice Act (CJA) came into effect on 1 April 2010 and provides measures for assessment, referral and management of children who are eligible for diversion. It also stipulates the options for diversion intervention. This study investigates the theoretical foundations, methods, value and limitations of four diversion strategies, namely lifeskills training, mentoring, outdoor intervention and family group conferencing. Attention is also paid to the interventions’ potential to realise the diversion aims of the CJA. Qualitative methods guided the research, in particular case study designs. A series of semi-structured interviews were conducted with the providers of the targeted diversion strategies. Programme documentation was also obtained in the form of training manuals and annual reports. In addition, interviews were conducted with Criminology and Social Work lecturers to further explore the theories that guide diversion strategies. Diversion programmes demonstrate particular understandings of the aetiology of child offending. The assumptions they make about the phenomenon to a large extent inform the methods used in the intervention process. Their assumptions include inadequate socialisation and personal abilities, absent and inimitable role models, negative life experiences and trauma, and reconciliation and reparation. Despite their unique assumptions, strategies appear to accommodate a fairly uniform profile of child offender. This raises questions about the assumptions of approaches regarding criminal behaviour vis-à-vis the risk factors they aim to address. Furthermore, parents feature as an important facilitator and inhibitor of diversion intervention. Their disinterest in or absence during significant intervention phases could restrict the outcomes and credibility of diversion programmes. Strategies that accommodate child offenders in groups are seemingly more inclined to exclude parents during the actual intervention. They may also fail to meet the individual intervention needs of participants as programmes are structured around a common goal for the group. Individual approaches, however, lack opportunities for vicarious learning. The time frames of diversion programmes and ad hoc followup procedures appear insufficient to optimally impact on criminal behaviour. Children who engaged in crime must acknowledge guilt for the offence in order to be diverted. Practice suggests that some children abuse the system in attempts to avoid formal prosecution. This could, in turn, compromise accountability which is a central aim of the CJA. Strategies show varying abilities to reintegrate diverted children with their families and communities. Moreover, only approaches that are fundamentally restorative in nature meaningfully involve the victims of offences. The lack of victim participation in diversion strategies fails to give effect to the reconciliation and reparation objectives of the CJA. Stigma stemming from contact with the criminal justice system appears difficult to avoid given the fixed location of service providers and some of the activities participants engage in. Despite these shortfalls, diversion shows promise in dealing with child offenders outside the ambit of formal justice procedures. It also prevents those who successfully complete the programmes from receiving a criminal record.

Die wegwending van kinders in konflik met die gereg word sedert die vroeg 1990s in Suid-Afrika beoefen. Sedertdien het die getal verwysings na en omvang van programme gefloreer ten spite van die afwesigheid van wette om wegwending te reguleer. Die Kinderregwet (Child Justice Act) het op 1 April 2010 in werking getree en voorsien maatreëls vir assessering, verwysing en bestuur van kinders wat vir wegwending kwalifiseer. Die wet stipuleer ook die opsies vir wegwending intervensie. Hierdie studie ondersoek die teoretiese onderbou, metodes, waarde en beperkinge van vier wegwendingstrategieë, naamlik lewensonderrig, mentorskap, buitelug en familie-groep beraadslaging. Aandag word ook geskenk aan die potensiaal van programme om die wegwendingsdoelwitte van die Kinderregwet te verwesenlik. Kwalitatiewe metodes is gevolg,spesifiek die gebruik van gevallestudie ontwerpe. ‘n Reeks semi-gestruktureerde onderhoud is met diensverskaffers van wegwending gevoer. Dokumentasie rakende die benaderings, spesifiek programhandleidings en jaarverslae, is ook bekom. Hierbenewens is onderhoude met Kriminologie en Maatskaplike Werk lektore gevoer ten einde die teorieë wat wegwending lei, verder te ondersoek. Wegwendingsprogramme het bepaalde opvattings rakende die etiologie van jeugoortreding. Hul aannames rakende die fenomeen gee grootliks rigting aan hul metodes van intervensie. Die aannames sluit in onvoldoende sosialisering en persoonlike tekortkominge in vaardighede, afwesige en onnavolgbare rolmodelle, negatiewe lewenservaringe en trauma, en hereniging en vergoeding. Ten spyte van hul unieke aannames blyk dit dat strategieë ‘n redelike uniform profile van jeugoortreder bedien. Hierdie waarneming bevraagteken hul aannames oor kriminele gedrag in lig van die risiko faktore wat hul poog om aan te spreek. Verder figureer ouers as beide fasiliteerders en inperkers van wegwending. Swak belangstelling of afwesigheid in belangrike fases van intervensies kan die uitkomste en geldigheid van wegwendingsprogramme kniehalter. Strategieë wat jeugoortreders in groepe akkommodeer blyk meer geneë te wees om ouers uit intervensies te laat. Hierdie tipe programme kan ook faal om die individuele behoeftes van jeugoortreders direk aan te spreek omrede intervensies rondom die behoeftes van die groep saamgestel word. Aan die ander kant laat individuele benaderings min ruimte vir plaasvervangende leer toe. Die tydsraamwerk van programme, asook hul ad hoc benaderings tot opvolgprosedures, blyk onvoldoende te wees om kriminele gedrag effektief aan te spreek. Kinders wat misdade pleeg moet skuld vir hul handelinge erken ten einde in wegwendingsprogramme opgeneem te kan word. Vanuit die praktyk blyk dit dat sommige kinders dié sisteem misbruik om formele aanklagte vry te spring. Hierdie realiteit kan aanspreeklikheid affekteer, wat ‘n sentrale doel van die Kinderregwet is. Die wegwendingstrategieë varieer in hul potensiaal om kinders met hul families en die gemeenskap te reïntegreer. Slegs benaderings wat essensieel op herstellende geregtigheid gebaseer is betrek slagoffers in die wegwendingsproses. Die afwesigheid van slagoffers in verskeie programontwerpe slaag moeilik daarin om die doelwitte van hereniging en vergoeding te bewerkstellig. Stigma wat spruit uit kontak met die regstelsel blyk moeilik voorkombaar te wees gegewe die plasing van diensverskaffers en sommige van die aktiwiteite wat jeugoortreders in programme onderneem. Ten spyte van hierdie tekortkominge hou wegwending die moontlikheid in om kinders buite formele regsprosedures te hanteer. Dit voorkom ook ‘n kriminele rekord in gevalle waar deelnemers hul programme voltooi.
Thesis (Ph.D. (Criminology))--University of the Free State, 2010
Keywords: Restorative justice; Nature-based / outdoor treatment; Mentoring; Lifeskills training; Family group conferencing; Child offender / juvenile delinquent; Child Justice Act; Diversion programmes; Diversion; Juvenile delinquency -- South Africa; Juvenile delinquency -- South Africa -- Prevention; Juvenile delinquency -- Rehabilitation -- South Africa; Recreation and juvenile delinquency; Life skills -- Study and teaching; Mentoring; Restorative justice -- South Africa